Low platelet counts after liver transplantation predict early posttransplant survival: The 60‐5 criterion. Issue 2 (21st November 2013) - Lesurtel, Mickaël; Raptis, Dimitri A.; Melloul, Emmanuel; Schlegel, Andrea; Oberkofler, Christian; El‐Badry, Ashraf Mohammad; Weber, Annina; Mueller, Nicolas; Dutkowski, Philipp; Clavien, Pierre‐Alain
<x xml:space="preserve">Abstract</x> Platelets play a critical role in liver injury and regeneration. Thrombocytopenia is associated with increases in postoperative complications after partial hepatectomy, but it is unknown whether platelet counts could also predict outcomes after transplantation, a procedure that is often performed in thrombocytopenic patients. Therefore, the aim of this study was to evaluate whether platelet counts could be indicators of short‐ and long‐term outcomes after liver transplantation (LT). Two hundred fifty‐seven consecutive LT recipients (January 2003‐December 2011) from our prospective database were analyzed. Preoperative and daily postoperative platelet counts were recorded until postoperative day 7 (POD7). Univariate and multivariate analyses were performed to assess whether low perioperative platelet counts were a risk factor for postoperative complications and graft and patient survival. The median pretransplant platelet count was 88 × 109/L [interquartile range (IQR) = 58‐127 × 109/L]. The lowest platelet counts occurred on POD3: the median was 56 × 109/L (IQR = 41‐86 × 109/L). Patients with low platelet counts on POD5 had higher rates of severe (grade IIIb/IV) complications [39% versus 29%, odds ratio (OR) = 1.09 (95% CI = 1.1‐3.3), P = 0.02] and 90‐day mortality [16% versus 8%, OR = 2.25 (95% CI = 1.0‐5.0), P = 0.05]. In the multivariate analysis, POD5 platelet counts < 60 × 109/L were identified as an independent risk factor for grade IIIb/IV complications [OR = 1.96 (95% CI = 1.07‐3.56), P = 0.03)], graft survival [hazard ratio (HR) = 2.0 (95% CI = 1.1‐3.6), P = 0.03)], and patient survival [HR = 2.2 (95% CI = 1.1‐4.6), P = 0.03)]. The predictive value of platelet counts for graft and patient survival was lost in patients who survived 90 days. In conclusion, after LT, platelet counts < 60 × 109/L on POD5 (the 60‐5 criterion) are an independent factor associated with severe complications and early graft and patient survival. These findings may help us to develop protective strategies or specific interventions for high‐risk patients. Liver Transpl 20:147‐155, 2014. © 2013 AASLD.